Rebondir après « l’échec » en centre de formation : analyse séquentielle des trajectoires socioprofessionnelles d’ex-apprentis footballeurs - Pierre-Cédric Tia (Temporalités)
To date, the professional future of ex-apprentice footballers, rejected by French academies, is a little-analyzed social phenomenon. The research carried out by Frederic Rasera (2010 ; 2014), exploring the individual, social conditions of vocation rebuilding by an ex-apprentice footballer, stands out as an exception. The present article means to contribute to the reflection relating to these young sportsmen. Through the study of the trajectories of twenty ex-apprentice footballers, we will see that it is possible to find biographical similarities characterizing their vocation rebuilding process. More precisely, we will show that an analysis in terms of lived temporalities (Dubar, 2014) makes it possible to reveal the resurgence of four life sequences (shock, perseverance, dilemma and metanoia) during their vocation rebuilding, thus revealing the collective dimensions attached to the process.